Psychological Contract and Apprenticeship Participation, and Papuan Ethnic Turnover Intention - Taime, Habel (SEIKO : Journal of Management & Business, 2023)
This study aimed to verify the role of the psychological contract and Apprenticeship Participation and Turnover Intention for Ethnic Papuans. This research was used through two psychological contract approaches: transactional and relational. The hypothesis of this study is the role of psychological contracts and the participation of the Nemangkawi Mining Institute IPN apprenticeship on Turnover Intention for Ethnic Papuans; the involvement in this study amounted to 110 apprenticeship participations that have been placed in several contracting companies and the privatization of Mimika district, the measuring instrument used is the Turnover Intention scale, psychological contracts, and apprenticeship participation scale—multiple regression analysis as the processing of the data obtained. The results of the multiple regression test showed a value of F = 25.273 at the significance level (p